Helminth reshapes host gut microbiota and immunoregulation by deploying an antimicrobial program of innate immunity - Yang Zou; Lixia Pu; Aijiang Guo; Yaqi Li; Yihui Liu; Yugui Wang; Yingying Ding; Xiaowei Du; Xiaola Guo; Shaohua Zhang; Xuepeng Cai; Shuai Wang (Gut Microbes, 2025)
Helminths can manipulate their host’s gut microbiota, with the expansion of the lactobacilli population being a common feature. This process profoundly influences host immunoregulation, yet the underlying mechanisms remain almost unknown. Using a tissue-dwelling helminth model (larval Echinococcus multilocularis) while validating key findings from other helminth infections, we show that helminths harness the antibacterial program of host innate immunity to transform the host gut microbiome and control gut microbiota-mediated immunity. Using multifaceted techniques, we elucidate that cathelicidin-related antimicrobial peptide (CRAMP), derived from the expanded CD11b+CD206+ macrophages rather than the intestinal epithelial cells, is the key component that enters into the gut ecological system and enhances the fitness of Lactobacillus by selectively killing gram-negative microbes like enterobacteria. Furthermore, through in vitro cell culturing and in vivo dietary intervention experiments, we demonstrate that this regulation from innate immunity is boosted via toll-like receptor signaling by helminth’s secretory products, which could be sufficiently tuned down by dietary vitamin D through its receptor and cyp27b1. Importantly, using microbiota-targeted treatment methods, we prove that this signaling bolsters gut microbiota-mediated host intestinal Foxp3+ Treg cell expansion and parasite survival and that therapies targeting this signaling are effective in treating infection. We outline a dietary micronutrient-dependent mechanism by which helminths leverage host innate immunity to edit the host gut microbiome and thereby control immunosuppression precisely.